2021
DOI: 10.1101/2021.07.18.451543
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relative contributions of sex hormones, sex chromosomes, and gonads to sex differences in tissue gene regulation

Abstract: Sex differences in physiology and disease in mammals result from the effects of three classes of factors that are inherently unequal in males and females: reversible (activational) effects of gonadal hormones, permanent (organizational) effects of gonadal hormones, and cell-autonomous effects of sex chromosomes, as well as genes driven by these classes of factors. Often, these factors act together to cause sex differences in specific phenotypes, but the relative contribution of each and the interactions among … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 59 publications
(105 reference statements)
1
9
0
Order By: Relevance
“…We focused on liver because of its central role in regulating homeostatic lipid levels and as the primary target for statin inhibition of cholesterol synthesis. Previous studies have identified significant sex differences in the hepatic transcriptome [26][27][28]. Our study extends and augments previous work by assessing the role of sex in hepatic gene regulation in physiological states that are relevant to human disease-hypercholesterolemia and statin treatment.…”
Section: Discussionsupporting
confidence: 69%
“…We focused on liver because of its central role in regulating homeostatic lipid levels and as the primary target for statin inhibition of cholesterol synthesis. Previous studies have identified significant sex differences in the hepatic transcriptome [26][27][28]. Our study extends and augments previous work by assessing the role of sex in hepatic gene regulation in physiological states that are relevant to human disease-hypercholesterolemia and statin treatment.…”
Section: Discussionsupporting
confidence: 69%
“…In female cells, biological processes belonging to cell organization and cell compartment are delayed, while in male cells, RNA and DNA related processes are delayed. Overall, our results reveal the emergence of early-acting sexual networks among males and females, thus, placing prominence on the role of sex chromosomes during early stages of organismal development 34,35 .…”
Section: Discussionmentioning
confidence: 67%
“…Because of the comparisons we had the capacity to make here, we cannot fully distinguish the relative importance of sex chromosomes, sex hormones and gonadal sex on driving sex differences in gene expression in the samples studied here. Recent work in adult tissues (liver and adipose) in a mouse model reports the strongest effect of activational hormones, followed by a lesser organizational gonad effect, with a third strongest role of sex chromosome complement on sex differences in gene expression (Blencowe et al, 2022). Thus, one can hypothesize that a similar hierarchy may be in place for shaping sex differences in gene expression in humans.…”
Section: Perspectives and Significancementioning
confidence: 99%
“…Further, a recent study of adult tissues from the Genotype-Tissue Expression Project (GTEx) demonstrated that sex influences gene expression and cellular composition throughout the body with 37% of all genes showing sex differences in expression in at least one tissue (Oliva et al, 2020). In mouse, chromosomal sex contributes, along with organizational gonadal sex and activational hormones, to sex differences in gene expression in adult tissues (Blencowe et al, 2022) in adult tissues. However, sex differences in early formed placental tissues have not been compared with sex differences in adult tissues.…”
Section: Introductionmentioning
confidence: 99%